Eksistensi Lembaga Keuangan Mikro dan Implikasinya Terhadap Sosial Ekonomi Masyarakat Dalam Perspektif Ekonomi Islam (Studi pada LKM Citra Abadi Desa Sidojangkung Kecamatan Menganti Kabupaten Gresik) - Hendro Rumpoko; Imam Darory (Fakultas Ekonomi Universitas Yos Soedarso, 2021)
Existence is existence, the existence of microfinance institutions in rural areas clearly has a role and implications for society. Especially in terms of socio-economic community. The existence of financial institutions, especially the banking sector, occupies a very strategic position in bridging the needs for working capital and investment in the real sector and ownership of funds. It is clear that the existence of microfinance institutions in rural areas has a very important role as a provider of services and financing. The formulation of the problem in this study is how the existence of microfinance institutions and their implications for the socio-economic community, whether there are differences in people's income before and after the existence of microfinance institutions, what is the view of Islamic economics regarding the existence of microfinance institutions and their implications for the socio-economic community. This research is classified into field research, the primary data is obtained from interviews while the secondary data is from documentation. In this study researchers used qualitative methods. The purpose of this study is to identify and explain the existence of microfinance institutions and their implications for the socio-economic community, and to find out how Islamic economics views the existence of microfinance institutions. Keywords: Micro; Field Research; Finance; Existence.